The resurgence of monkeypox virus: a critical global health challenge and the need for vigilant intervention - Malla, Ashwini; Saleh, Fayez M. (Frontiers in Public Health, 2025)
The resurgence of the monkeypox virus (MPXV), a zoonotic Orthopoxvirus historically regarded as endemic to the tropical rainforests of Central and West Africa, represents a significant and evolving global health challenge. Waning Orthopoxvirus immunity following the cessation of smallpox vaccination and inequitable vaccine access have increased susceptibility, especially in resource-limited settings. Combined with urbanization, environmental degradation, global travel, and human-wildlife interactions, these factors have driven MPXV beyond its traditional regions. Notably, recent outbreaks in non-endemic countries have exhibited a distinct epidemiological shift, with a higher incidence among men who have sex with men, often in the absence of travel history to endemic areas, underscoring evolving transmission dynamics. This review provides a comprehensive examination of MPXV’s epidemiology, clinical features, and transmission mechanisms, highlighting the complexities of its containment. Key challenges—including surveillance gaps, vaccine inequities, and limited access to diagnostics and therapeutics—are compounded by unresolved controversies over MPXV’s natural reservoirs and respiratory transmissibility, as well as critical research gaps in zoonotic spillover mechanisms and long-term immunity. Addressing these issues demands global collaboration to leverage next-generation vaccines and antivirals, paired with an integrated public health response: enhanced surveillance, targeted education, and equitable resource allocation. Sustaining these efforts is vital to curbing MPXV’s resurgence and preventing its entrenchment as a global health threat.